2022
DOI: 10.1177/19417381221128822
|View full text |Cite
|
Sign up to set email alerts
|

Individual-Specific Relationship Between External Training and Match Load and Creatine-Kinase Response in Youth National Team Soccer Players

Abstract: Background: Previous studies have examined the relationship between external load and creatine-kinase (CK) response at the team level. This study aimed to build individualized CK prediction models for elite youth national team soccer players. Hypothesis: The CK response of youth soccer players can be categorized as being sensitive to micromovements (MM), high-velocity (HV) parameters, or the combination of both, measured during training sessions and matches. Study Design: Prospective cohort study. Level of Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While this approach shows promise for monitoring individual CK values in athletes, it may not be intuitive for professionals to implement, and the requirement for prior individualized values can present a challenge. Lastly, based on previous research focused on associations between external load metrics and CK values at team level ( Hader et al, 2019 ; Wiig et al, 2019 ), models aimed to predict individualized CK values have been recently reported ( Schuth et al, 2022 ). Identifying which load parameters best correlate this marker is important ( Schuth et al, 2022 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
See 1 more Smart Citation
“…While this approach shows promise for monitoring individual CK values in athletes, it may not be intuitive for professionals to implement, and the requirement for prior individualized values can present a challenge. Lastly, based on previous research focused on associations between external load metrics and CK values at team level ( Hader et al, 2019 ; Wiig et al, 2019 ), models aimed to predict individualized CK values have been recently reported ( Schuth et al, 2022 ). Identifying which load parameters best correlate this marker is important ( Schuth et al, 2022 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
“…Lastly, based on previous research focused on associations between external load metrics and CK values at team level ( Hader et al, 2019 ; Wiig et al, 2019 ), models aimed to predict individualized CK values have been recently reported ( Schuth et al, 2022 ). Identifying which load parameters best correlate this marker is important ( Schuth et al, 2022 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
“…In addition, an understanding of load dynamics across training and competition is presented as an important aspect related to performance enhancement in team sports (8,47,60,61), showing, for example, how adjusting specific drills such as large,-medium-and small-sided games may help replicate game demands (86,87). Correlations between EL and IL in different season periods were applied in order to understand the fluctuation of some metrics such as players' strength (88), players' recovery (89), or ACWR, between players' positions, starters, and non-starters (82, 84,90,91). Also, Pizarro et al (26) demonstrated how different occupational areas may promote different physical variables.…”
Section: Applicability Of the Tracking System Related To The Performa...mentioning
confidence: 99%
“…More recently, performance analysis research is stepping forward on the understanding of HIAs and on predictive studies for fatigue and match performance. The literature suggests that during different phases of a training cycle, such as the baseline or competition phase, training loads must be modulated to either enhance or reduce fatigue levels (89). In the light of this, it is important to understand the match HIA in order to manage fatigue properly, matching both variables to adaptation to training and for achieving competitive performance (10,40).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation